Uma proposta de índice de precarização para o mercado de trabalho da região metropolitana de São Paulo - Oliveira, Marcos Paulo de (2011)
This study aim to present a proposal of a tendency index of precariousness for the labor market at the metropolitan area of the city of São Paulo, Brazil. With this Index we intend to understand the changes of the labor scenario and the shifts to the precariousness of its conditions. Between the years of 1945 and 1973, the golden years of the capitalism, there was a better way of occupational insertion due to the low index of unemployment. In this time, we also notice the increasing of the remuneration with real increasing gains, the increasing of the unionisation and the generalised social protection. In this scenario, the workers change their role to a consumption role. This was a right guaranteed by the workplace. This right means social identity, the feeling of belong a specific community. In this time, it was identify the foundation of labor market regulation institutes: the labor market guarantees the income; it allows the workman to spend the money at the market, and then the money returns to a new cycle of production and investment. In the mid-1970 and in the 1980s there was the productive restructuring process follow by the financialization of the main developed economies. In Brazil, in the 90s, there is a strong tendency of flexibility and precariousness of the labor, mainly at the beginning of the deployment and implementation of the Plano Real, at the government of Fernando Henrique Cardoso (1995-1998 and 1999-2002). In this period there was a low economic growth, increasing the unemployment situation and decreasing of the labor income. The question of this research was guided by the characteristics of the government of the president Luis Inácio Lula da Silva (2003-2006 and 2007-2009). The president was a workman at the metallurgy industry and has great experience at the labor union movements. There for, would be sustained the tendency of precariousness of the labor? To answer this question, this research argues the construction of Tendency Index of Precariousness (TIP) of the labor market of the metropolitan area of Sao Paulo, during the 1995 to 2009, using the Human Development Index method to build the TIP. The results show that the use of the TIP is significant. The TIP is a statistic tool which shows direction of the variables that evolve in different and reverse ways. It is a value instrument for the analyses of the evolution of the condition of insertion at the labor market of the metropolitan area of Sao Paulo. The results of the TIP show the increase of the precariousness of the labor market between the years of 1995-2003 and a tendency of decrease of precariousness between the years 2004-2009